In vivo Recording Quality of Mechanically Decoupled Floating Versus Skull-Fixed Silicon-Based Neural Probes - Chauvière, Laetitia; Pothof, Frederick; Gansel, Kai S.; Klon-Lipok, Johanna; Aarts, Arno A. A.; Holzhammer, Tobias; Paul, Oliver; Singer, Wolf J.; Ruther, Patrick (Frontiers in Neuroscience, 2019)
Throughout the past decade, silicon-based neural probes comprising sophisticated integrated CMOS electronics providing a large number of recording sites along slender probe shanks have become a driving force in neural engineering. Using such neural probes in a chronic setting often requires them to be mechanically anchored with respect to the skull. However, any relative motion between brain and implant causes recording instabilities and tissue responses such as glial scarring, thereby shielding recordable neurons from the recording sites integrated on the probe and decreasing the signal quality. In the current work, we present we present a comparison of results obtained using mechanically fixed and floating silicon neural probes implanted into the cortex of a non-human primate. We demonstrate that the neural signal quality of the floating probe is initially superior to the fixed device. Nonetheless, the skull-fixed probe also allowed long-term recording of multi-unit activity and low frequency signals over several months, especially once pulsations of the brain were properly controlled.